VirtuMath: The Needs of Assistive Technology in Mathematics Learning for Students with Deaf-Mute Disabilities - Suarjana, I Made; Simamora, Alexander Hamonangan; Antara, I Gede Wahyu Suwela (Indonesian Journal of Instruction, 2025)
Students with deaf-mute disabilities in inclusive elementary schools often face significant barriers in accessing verbal instruction, particularly in subjects that require abstract reasoning such as mathematics. This study aims to explore the difficulties in learning mathematics experienced by students with deaf-mute disabilities in inclusive elementary schools and analyze the need for the use of assistive technology to support their learning. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews and classroom observations. The research participants consisted of one teacher, two hearing impairment students, two parents, and one principal. Data analysis was carried out using the data triangulation method. The results of the study indicate that students with deaf-mute disabilities have difficulty in understanding mathematical concepts that are delivered verbally, especially in abstract terminology. The findings also reveal that visual and interactive assistive technology is needed to help students understand mathematics material better. Teachers, parents, and students expect technology that combines animation, video, interactive images, and physical devices that support direct interaction with learning materials. Based on these findings, VirtuMath, as an assistive technology that integrates visual and sensory representations, is proposed as a potential solution to support mathematics learning for hearing impairment students.